The Shadow Economy : an International Survey. - Schneider, Friedrich (Cambridge University Press, 2003)
Illicit work, social security fraud, illegal employment and economic crime have always existed, but they are now on the increase. Most governments try to reduce the shadow economy through punitive measures or through education. This book suggests a reform of state institutions, to improve the dynamics of the official economy.